Polymorphism of genes of hemostasis system, endothelial dysfunction and regulation of blood pressure in pregnant woman with preeclampsia and fetal growth retardation - T. O. Loskutova (Patologìâ)
Objective: To study the distribution and effect of blood clotting, endothelial dysfunction, and blood pressure regulator gene polymorphisms on the development of fetal growth retardation in women with preeclampsia (PE).